URGENSI PEMBUKTIAN DALAM PERSIDANGAN TINDAK PIDANA ELEKTRONIK - Hizkia Andhitya Wijaya; Muhammad Rustamaji (Verstek, 2023)
This article analyzes the urgency of the evidentiary process in electronic criminal trials. This study aims to determine the importance of the evidentiary process in an electronic crime trial where in an electronic crime the evidence submitted is not only tangible but intangible evidence. This research is a normative legal research that is prescriptive and applied. The legal material collection technique used in this study is the document study technique or library study technique. The collection of legal materials is carried out through document studies and literature studies. Based on the results of the research, it shows that proof in electronic crime is the main thing, because in the proof what is sought is material truth, that a crime has occurred and it is the defendant who is guilty of committing it. The court is bound by a rule or methods or provisions of evidence as stipulated in the law. Legitimate evidence must be carried out in court in accordance with the procedures or methods that apply in the law of evidence.Keywords: Evidence, Electronic Crime, Criminal Procedure law